2019
DOI: 10.1111/jvim.15572
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of benazepril in cats with heart disease in a prospective, randomized, blinded, placebo‐controlled clinical trial

Abstract: BackgroundHeart disease is an important cause of morbidity and mortality in cats, but there is limited evidence of the benefit of any medication.HypothesisThe angiotensin‐converting enzyme inhibitor benazepril would delay the time to treatment failure in cats with heart disease of various etiologies.AnimalsOne hundred fifty‐one client‐owned cats.MethodsCats with heart disease, confirmed by echocardiography, with or without clinical signs of congestive heart failure, were recruited between 2002 and 2005 and ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…In 2 randomized, placebo‐controlled studies, neither an angiotensin converting enzyme (ACE) inhibitor (ramipril) nor spironolactone had any effect on LV mass or diastolic function in cats with subclinical HCM, but study populations were small and limited to cats of a single breed that had heritable cardiomyopathy . Similarly, benazepril had no effect on time to treatment failure compared to placebo in a randomized placebo‐controlled study that included cats with subclinical heart disease . No studies have been reported of pimobendan use in cats with subclinical cardiomyopathy.…”
Section: Treatmentmentioning
confidence: 99%
See 2 more Smart Citations
“…In 2 randomized, placebo‐controlled studies, neither an angiotensin converting enzyme (ACE) inhibitor (ramipril) nor spironolactone had any effect on LV mass or diastolic function in cats with subclinical HCM, but study populations were small and limited to cats of a single breed that had heritable cardiomyopathy . Similarly, benazepril had no effect on time to treatment failure compared to placebo in a randomized placebo‐controlled study that included cats with subclinical heart disease . No studies have been reported of pimobendan use in cats with subclinical cardiomyopathy.…”
Section: Treatmentmentioning
confidence: 99%
“…Measurement of serum creatinine, blood urea nitrogen, and electrolyte concentrations is recommended 3‐7 days after initiating furosemide (LOE low). Angiotensin converting enzyme inhibition with benazepril did not delay the onset of treatment failure in a randomized, placebo‐controlled study of cats with CHF (LOE high) although ACE inhibitors still are used by some cardiologists. Prophylactic antithrombotic treatment with clopidogrel (18.75 mg/cat PO q24h, with food) is recommended in any cat with a history of CHF and moderate to severe LA enlargement (LOE low).…”
Section: Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“… 200 , 201 One study found no benefit; however, it included cats that were not in heart failure and so the strength of its conclusions is limited. 202 In general, the number of medications administered to a cat in heart failure should be minimized to reduce stress. In the authors’ opinion, one drug that might be safely eliminated, if elimination of a drug might be beneficial in this regard, is the ACE inhibitor.…”
Section: Treatmentmentioning
confidence: 99%
“…7,8 Unlike ACE, which cleaves 2 amino acids, ACE2 removes a single amino acid from AT1 and AT2, forming angiotensin 1-9 (Ang1-9) and angiotensin 1-7 (Ang1-7), respectively ( Figure 1). Despite a structural difference of just 1 amino acid, Ang1-7, Ang1-9, and other APs such as angiotensin [1][2][3][4][5] are vasodilatory, natriuretic, and cardioprotective. 9 This discovery has expanded our understanding of the AP system and use of traditional RAASi drugs, such as ACEI, beyond just AT1 and AT2.…”
Section: Introductionmentioning
confidence: 99%